Spatial distribution, emission source and health risk of parent PAHs and derivatives in surface soils from the Yangtze River Delta, eastern China. (July 2017) - Cai, ChuanYang; Li, JingYa; Wu, Di; Wang, XiLong; Tsang, Daniel C.W.; Li, XiangDong; Sun, JianTeng; Zhu, LiZhong; Shen, HuiZhong; Tao, Shu; Liu, WenXin
Abstract: 243 surface soil samples were collected from the Yangtze River Delta (YRD) region, and the concentration distributions and compositional profiles of 27 parent PAHs (PPAHs), nitro- and oxy-derivatives (NPAHs and OPAHs), respectively, and health risk of 16 PPAHs were determined. Atmospheric samples were collected at two sites with high topsoil concentrations of PAHs to assist in identifying the emission sources of PPAHs. The total concentrations of PPAHs, NPAHs and OPAHs fell in the ranges of 21.0–3563.2 ng/g, 0.4–4.6 ng/g and 2.1–834.1 ng/g, respectively. PPAHs in topsoil were dominated by low and medium molecular weight species. The main components of OPAHs were 9FO and ANQ. For NPAHs, only 1N-NAP was frequently detected. Overall, the northern parts of the YRD region were more heavily contaminated by PPAHs and their corresponding derivatives. The soil TOC fraction and GDP per capita were significantly correlated with the spatial distribution of PPAHs. Specific ratios of isomeric species and principal component analysis (PCA) designated combustion of industrial coal and biomass, and traffic exhaust as the main mixed emission sources of PPAHs in surface soils in this region. The detected NPAHs and OPAHs were significantly associated with the corresponding PPAHs. The estimated incremental lifetime cancer risk attributed to 16 PPAHs in surface soil was greater than 10 −6, indicating a potential risk of contracting cancer by exposure to topsoil from the YRD region. The cumulative probability of cancer risk for both adults and children via three exposure pathways followed the sequence of dermal contact > ingestion > inhalation. Graphical abstract: Highlights: High levels of PPAHs and derivatives in topsoil occurred in northern part of YRD. Significant correlations of soil TOC fractions with concentrations of PPAHs. Source diagnostics of PPAHs by isomeric ratios, PCA, MLR and emission inventory. Close associations of NPAHs and OPAHs with corresponding PPAHs in topsoil. Cumulated probability of cancer risk showed dermal contact > ingestion > inhalation.